Frequency Variation of the AC Order Parameter Susceptibility of the Metamagnetic Ising Model - Gul Gulpinar (Advances in Condensed Matter Physics)
The extensive investigation of the absorptive and reactive parts of the AC order parameter susceptibility spectra of iron group dihalides, which is obtained on the basis of Onsager theory of irreversible processes, revealed the fact that the diagonal phenomenological rate coefficients γs and γm have an important impact on the nature of the order parameter relaxation process. The number of the relaxation peaks appearing in the double logarithmic plots of χs′′ versus field frequency ω and the number of plateau regions in χs′ spectrum depends on the values of γs and γm. Only for γs≫γm does the relaxation evolve from a simple Debye exponential at high temperatures to a two-step process at lower temperatures in which there exist two long relaxation times characterizing the relaxation of staggered magnetization. In parallel with these characteristics of the order parameter relaxation, Cole-Cole plots (χs′′-χs′) are shown to consist of two arcs in the metamagnetic phase and of a semicircle in the paramagnetic phase.